Dilema Pengangguran di Era Digital: “A Recent True Story from Indonesian Jobseekers” - Anwar, Ravel; Marliani, Sonnya; Hadi, Rachman (Malaqbi Publisher, 2024)
This study examines the challenges and strategies faced by job seekers in the digital era through a qualitative analysis of personal narratives and real-life experiences. By conducting in-depth interviews and collecting personal stories from individuals such as Rina, Ahmad, and Lisa, this research reveals the skills mismatch between formal education and industry needs, the challenges of adapting to recruitment technologies, and the significance of a robust portfolio and professional networking. The findings indicate that job seekers experience considerable pressure in an increasingly competitive labor market. To address these issues, the study recommends curriculum reforms in education to align more closely with industry requirements, enhanced access to digital skills training, and adjustments to recruitment processes to be more inclusive. Furthermore, practical experience and career mentoring are critical factors in preparing a competitive workforce. The limitations of this research include the subjectivity of the qualitative approach and the challenges of generalizing the findings. Therefore, further studies employing quantitative methods and research across various regions in Indonesia are necessary to strengthen the validity and reliability of these findings. This research provides valuable insights for policymakers, educational institutions, and job seekers in designing effective strategies to tackle unemployment and enhance workforce skills in the digital era. Consequently, close collaboration among government, industry, and educational institutions is essential to create a more inclusive and adaptive employment ecosystem in response to technological changes and labor market dynamics.